2019
DOI: 10.1002/ppul.24382
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of spirometry vs impulse oscillometry: A comparative study in children with sickle cell disease

Abstract: Background Spirometry is conventionally used to diagnose airway diseases in children with sickle cell disease (C‐SCD). However, spirometry is difficult for younger children to perform, is effort dependent, and it provides limited information on respiratory mechanics. Impulse oscillometry (IOS) is an effort‐independent pulmonary function test (PFT), which measures total airway resistance (R5Hz) and reactance (AX). IOS could be advantageous without certain limitations of spirometry. Aim To compare the accuracy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
0
17
1
1
Order By: Relevance
“…100 Although it's not an adult-based study, a group of researchers from Pennsylvania found that oscillometry was more feasible than spirometry in children with Sickle-Cell disease, because it can be performed on children of young age, and it has greater sensibility to bronchodilatationresponse. 101…”
Section: Neuromuscular Diseasesmentioning
confidence: 99%
“…100 Although it's not an adult-based study, a group of researchers from Pennsylvania found that oscillometry was more feasible than spirometry in children with Sickle-Cell disease, because it can be performed on children of young age, and it has greater sensibility to bronchodilatationresponse. 101…”
Section: Neuromuscular Diseasesmentioning
confidence: 99%
“…Machine learning (ML) is an algorithm-based novel modeling technique that has been introduced recently to select key behavior features (biomarkers) and predict risk levels [29]. ML methods are more precise and accurate in terms of prediction abilities compared with traditional statistical methods, because complex intervariable interactions are taken into account in ML only [30].…”
Section: Application Of Different ML Algorithmsmentioning
confidence: 99%
“…In adults, IOS was found to be correlated with spirometry results but was not found to be correlated with asthma control 20 . Measurements of R5Hz and AX have been found to be more sensitive to bronchodilator response compared to FEV1 values in children 21 . Similarly, in our study asthma control was significantly worse in overweight/obese children but this was not reflected on the IOS measurements of resistence.…”
Section: Discussionmentioning
confidence: 98%